Scribal practice, text and canon in the Dead Sea scrolls essays in memory of Peter W. Flint - Collins, John J. 1946-; Geyser-Fouché, Ananda; Flint, Peter W. 1951-2016 (Boston BRILL, 2019)
Intro -- Contents -- Figures and Tables -- Notes on Contributors -- Introduction Peter Flint in Memoriam -- Part 1 Text and Canon -- Chapter 1 Qumran Evidence for the Text and Canon of the Bible -- Part 2 Text-Critical Studies -- Chapter 2 Hebrew Bible Textual Criticism and the Dead Sea Scrolls: What Not to Expect of the Pesher Habakkuk (1QpHab) -- Chapter 3 4QLXXNum and a Text-Critical Examination of a Debated Hebrew Term in Numbers 4 -- Chapter 4 The Ezekiel Manuscripts from the Dead Sea, the Ancient Versions, and the Textual History of Ezekiel -- Chapter 5 On "True" Editions: Pluriformity and Authority between Psalms and Serekh -- Chapter 6 A Textual Analysis of Pseudo-Ezekiel (4Q385 and 4Q386): Rewritten or Merely Copies of Each Other -- Chapter 7 Nebuchadnezzar Found and Forgotten: a New Fragment of 4Q385a (4QApocryphon of Jeremiah Ca) 18 i -- Part 3 Canon and Authority -- Chapter 8 Uses of Earlier Literature in Some Second Temple Texts -- Chapter 9 An Examination of the Songs of Ascents and Psalm 119 in 11QPsa -- Part 4 Scribal Practice -- Chapter 11 The Grain of the Kittim in the Habakkuk Pesher: a New Reading of 1) ומאכלו ברו QpHab 6:5) -- Chapter 12 The Vistas of Variant Readings: Towards an Understanding of Scribal Transmissionas Reception in the Qumran Fragments of Aramaic Daniel -- Chapter 13 Exegesis of the Bible Enriched by the Dead Sea Scrolls -- Chapter 14 The Excerpted Manuscripts from Qumran, with Special Attention to 4QReworked Pentateuch D and 4QReworked Pentateuch E -- Part 5 Language -- Chapter 15 Trajectories of Diachronic Change in Qumran Hebrew: Evidence from the Negative Existential in Post-Predicate Position -- Part 6 Thematic Studies -- Chapter 16 The Star of Balaam and the Prophecy of Josephus concerning Vespasian -- Chapter 17 Lady Metaphors in Judaic Wisdom Literature -- Index of Modern Authors.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books; Festschrift